Relationship Between the Practice of Physical Activity and Physical Fitness in Physical Education Students: The Integrated Regulation As a Mediating Variable - Gea-García, Gemma María; González-Gálvez, Noelia; Espeso-García, Alejandro; Marcos-Pardo, Pablo J.; González-Fernández, Francisco Tomás; Martínez-Aranda, Luis Manuel (Frontiers in Psychology, 2020)
The practice of physical activity contributes to the prevention of chronic diseases such as obesity, metabolic syndrome or cardiovascular diseases, being also directly related to the individual's physical fitness. Therefore, it is necessary to measure and monitoring the levels of physical activity in childhood and adolescence, since it may be useful to describe their current health status and the association with physical fitness, as well as to reveal putative consequences in the future. Within the educational field, it has been shown that physical education classes are a favorable context for the creation of healthy physical-sports habits and self-determined motivation could be a key for explaining the level of physical activity practice. For this reason, the purpose of this research was to study the mediating role of integrated regulation (IR) on the relationship between physical activity and physical fitness in children and adolescents. A total of 325 students between 11 and 14 years old participated in the study. The level of physical activity was estimated through the specific Physical Activity Questionnaire for Children (PAQ-C), while motivation and IR were measured by using the Perceived Locus of Causality scale (PLOC-2). In addition, physical fitness was measured through the Eurofit fitness battery of tests, composed of three body composition measures and seven tests of different physical capacities. The physical fitness score showed no differences when genders were compared. After regression analysis, the resulting models revealed a good adjustment and correlation between physical activity practice and physical fitness (β=0.173; p<0.001), being established through the macro Proccess that this relationship is partially conditioned by the IR (β=0.122; p=0.03). ROC curve analysis estimated the score of 5.88 as a cut-off point to discriminate between levels of IR for students, classified as physically active or not (AUC=0.67; p<0.001). The conclusions from these main and other complementary analyses reporting complete mediations, suggest that the IR could be decisive in predicting and explaining the relationship between the practice of physical activity and physical fitness at these ages, highlighting its importance for a greater adherence to the practice.